2013
DOI: 10.4103/1947-2714.106208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total antioxidant capacity of saliva in type 2 diabetic patients with and without periodontal disease: A case-control study

Abstract: Background:Diabetes mellitus (DM) has been linked with oxidative stress and decreased antioxidant defense. A connection has been established between diabetes and periodontal disease.Aim:The aim of present study was to compare salivary total antioxidant capacity of type 2 DM patients and healthy subjects with and without periodontal disease.Materials and Methods:A total of 120 subjects consisting of 30 type 2 DM patients with periodontal disease; 30 type 2 DM patients without periodontal disease; 30 healthy sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
3
28
1
4
Order By: Relevance
“…Therefore, the co-existence of both conditions could pathologically increase the effect of oxidative stress. [3839] In DN, excessive free radical generation has been shown to decrease the activities of antioxidant enzymes. The decrease in the GSH and GPx level was correlated with GR activity in DN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the co-existence of both conditions could pathologically increase the effect of oxidative stress. [3839] In DN, excessive free radical generation has been shown to decrease the activities of antioxidant enzymes. The decrease in the GSH and GPx level was correlated with GR activity in DN.…”
Section: Discussionmentioning
confidence: 99%
“…found that the total antioxidant capacity is inversely proportional to the severity of inflammation and can be used as an useful marker of periodontitis in health and diabetic patients. [4] However, it is also conceivable that HA administration to periodontal wound sites could achieve beneficial effects in periodontal tissue regeneration and periodontal disease treatment. [5]…”
Section: Introductionmentioning
confidence: 99%
“…For instance, glucose-containing carbonated soft drinks increase carbonyl stress burden (3) , which, in turn, may result in a decrease in antioxidant concentration in oral saliva (4) and enhance oxidative nitration in association with the inflammatory reaction (5) . From the biological viewpoint, the inflammatory reaction caused by such oxidative stress is highly associated with systemic diseases, such as metabolic syndrome, diabetes, hypertension, asthma and periodontal disease (PD) (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) . Oxidative stress (2,3,6,8,9,(13)(14)(15) pertaining to PD may be mediated through advanced glycation end-products that are created through non-enzymatic pathways from monosaccharide substances, dicarbonyls originating from the Maillard reaction, sugar self-oxidation and other molecular pathways (16,17) .…”
mentioning
confidence: 99%